IMPACT EVALUATION OF SGSY ON SOCIO-ECONOMIC DEVELOPMENT OF RURAL POOR IN ASSAM - Violina Gogoi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Since the inception of economic planning in India, the first five year plan introduced the Community Development Programme (CDP) and on 2nd October 1952, the first 55 Community Development Projects were inaugurated where each project was having 3 Development Blocks. With the passage of time, more and more such projects were developed. The Community Development Programme had undertaken ambitious schemes for all round development of rural areas which included improvement of agricultural techniques, exploring supplementary sources of employment, extension of minor irrigation facilities, provision for social services and development of Co-operatives and Panchayat. The present study made an attempt to examine one major rural development programme namely Swarnajayanti Gram-Swarozgar Yojana (SGSY) in Assam with special reference to Dibrugarh and Sivasagar districts of Assam. The study aims to examine the objectives, achievements as well as the problems and prospects of SGSY. The basic objectives of the present study is to find out actual implementation of SGSY in the study and to assess the impact of SGSY on increasing income of rural people i.e. the selected beneficiaries.